2015
DOI: 10.1007/s11113-015-9380-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative Cohort-Component Models for Local Area Population Forecasts

Abstract: It is generally accepted by demographers that cohort-component projection models which incorporate directional migration are conceptually preferable to those using net migration. Yet net migration cohort-component models, and other simplified variations, remain in common use by both academics and practitioners because of their simplicity and low data requirements. While many arguments have been presented in favour of using one or other type of model, surprisingly little analysis has been undertaken to assess w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
(34 reference statements)
0
36
0
Order By: Relevance
“…Unfortunately, these data are not easy to obtain for many countries because of the reluctance of official statistics agencies to publish very detailed data matrices due to the risk of disclosure of individuals, and sampled data are usually not of sufficient size to capture the relatively small numbers of people moving between regions. (1976), Rees (1997), Wilson and Bell (2004), and Wilson (2016).…”
Section: Origin Dependence In Migration Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these data are not easy to obtain for many countries because of the reluctance of official statistics agencies to publish very detailed data matrices due to the risk of disclosure of individuals, and sampled data are usually not of sufficient size to capture the relatively small numbers of people moving between regions. (1976), Rees (1997), Wilson and Bell (2004), and Wilson (2016).…”
Section: Origin Dependence In Migration Flowsmentioning
confidence: 99%
“…Fortunately, there are some examples of very large and detailed population projections from which we can draw experiences from, notably Wilson () for local areas in New South Wales, Australia, Rees, Wohland, Norman, and Boden () for ethnic projections across local authorities in the United Kingdom, and Lutz, Butz, and KC () for human capital projections for all countries in the world. See also Rogers (), Rees (), Wilson and Bell (), and Wilson ().…”
Section: Issues In Applied Multiregional Demographymentioning
confidence: 99%
“…However, for areas experiencing population declines, CCDs have the potential of creating impossible negative populations through linear decline. In this work, I use a blended approach in which CCDs in areas projected to increase and CCRs in areas projected to decrease create more utility in the projections, preventing impossible negative populations and explosive population growth, and previous research has shown blended linear/exponential population projections outperform both linear and exponential models, respectively (Wilson 2016).…”
Section: Cohort Change Differencesmentioning
confidence: 99%
“…Blended linear/exponential demographic projections tend to outperform both linear and exponential models, respectively (Wilson 2016). This technique has all of the advantages of CCRs by remaining just as simple and parsimonious with minimal data requirements while producing projected populations without impossibly explosive growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation